Comparative Analysis of Thermal Performance and Induced Stresses in TIG and MIG Welding Processes Using Numerical Simulation - صالح عبدالقادر صالح فرج; ناصر فضل الله فرج عبدالعزيز; جمعة الناجي محمد آدم; بريك الناجي محمد ادم (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to provide a comprehensive comparison between Tungsten Inert Gas (TIG) welding and Gas Metal Arc (MIG) welding in terms of thermal behavior, energy transfer efficiency, and their effects on the thermal structure of medium-carbon steel (AISI 1045). The analysis combines theoretical evaluation with three-dimensional numerical thermal simulation using the SimScale platform, aiming to examine temperature distribution across the welded joint and to determine the size and characteristics of both the fusion zone and the heat-affected zone. Representative thermal parameters such as voltage, current, and welding speed were selected based on data reported in scientific databases including ScienceDirect and ResearchGate. The results showed that MIG welding generates approximately 30% higher heat input than TIG welding, leading to deeper penetration and a wider heat-affected area. In contrast, TIG welding provides better heat concentration and lower thermal distortion, making it more suitable for precision and high-surface-quality applications. The findings demonstrate that the optimal choice of welding technique depends on the specific industrial application, required thermal control, and surface quality standards. Moreover, the study highlights the importance of numerical simulation in predicting thermal behavior prior to practical welding operations. These results establish a strong foundation for developing more advanced models that integrate thermal and mechanical analyses in future welding research